Interrelations in Saudi Stocks Market - Eltahir, Yassin; Klabi, Fethi; Sallam, Osama Azmi; Osman, Hussien Omer (International Journal of Economics and Financial Issues, 2019)
This study asks about the existence of co-variances and correlations among variances in the Saudi stock returns and aims at knowing which stocks are the most closely related to other stocks. A sample of five stocks representing basic materials, banking, services, food and transport sectors and reflecting the main trends in the Saudi market were selected (SABIC, Al Rajhi, Etisalat, Almarai and Al Bahri respectively). Daily stock returns were collected during the period from 2011 to 2016, representing the life of the five-year plan. The authors used the MARCH-DVEC methodology to estimate the variances and correlations of stock return variances, considering the interactions of stock return variances. The results confirmed the existence of positive co-variances and correlations between stock returns. Al Rajhi, Sabic and Etisalat stock returns showed the largest co-variances and correlations. The general trend values of co-variances indicated positive growth except for Al Bahri. This study concluded that relations between Saudi stocks are stable over time, confirming the Saudi stocks market stability. Keywords: Stock return variance, M GARCH-VEC, Correlation, Co-variance JEL Classifications: C130; C49 ; G10 DOI: https://doi.org/10.32479/ijefi.7542